2011
DOI: 10.1021/jp109993a
|View full text |Cite
|
Sign up to set email alerts
|

Plasmon-Enhanced Resonance Energy Transfer from a Conjugated Polymer to Fluorescent Multilayer Core−Shell Nanoparticles: A Photophysical Study

Abstract: The influence of metallic silver nanoparticles on F€ orster resonance energy transfer (FRET) between a watersoluble cationic conjugated polymer and fluorescent multilayer Ag@SiO 2 @SiO 2 þFiTC core-shell nanoparticles was characterized using a combination of light scattering and luminescence techniques. Positioning the fluorescent polymer 7 nm away from the surface of a 45 nm silver nanoparticle with a silica spacing layer increases its quantum yield to 77%, as compared to 3% when measured as an isolated emitt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
56
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 75 publications
(57 citation statements)
references
References 45 publications
1
56
0
Order By: Relevance
“…6,[19][20][21][22][23][24][25][26][27][28][29] LSP coupled FRET has been observed using single metallic nanoparticles coupled to a single donor-acceptor pair 6 , core-shell structures [23][24][25] and planar structures. [26][27][28] Studying FRET from a conjugated polymer to fluorescent multilayer core-shell NP, Lessard-Viger et al observed a 70% increase in the Förster radius and an increase in the FRET-rate by two orders of magnitude.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…6,[19][20][21][22][23][24][25][26][27][28][29] LSP coupled FRET has been observed using single metallic nanoparticles coupled to a single donor-acceptor pair 6 , core-shell structures [23][24][25] and planar structures. [26][27][28] Studying FRET from a conjugated polymer to fluorescent multilayer core-shell NP, Lessard-Viger et al observed a 70% increase in the Förster radius and an increase in the FRET-rate by two orders of magnitude.…”
Section: Introductionmentioning
confidence: 99%
“…[26][27][28] Studying FRET from a conjugated polymer to fluorescent multilayer core-shell NP, Lessard-Viger et al observed a 70% increase in the Förster radius and an increase in the FRET-rate by two orders of magnitude. 24 Also using a core-shell geometry, composed of donor and acceptor fluorophore molecules embedded in a shell coating a Au-Ag core-shell nanocrystal, Wang et al demonstrated that FRET could be switched on and off by varying the spectral position of the LSP resonance relative to the donor emission and acceptor absorption. 25 LSP coupled FRET was reported in planar structures comprised of a layer of dyes and/or QDs, acting as donors and acceptors, placed on a MNP layer.…”
Section: Introductionmentioning
confidence: 99%
“…For example, we measured an average fluorescence lifetime of 0.228 ns for eosin in core-shell NPs with a 7 ± 2 nm thick spacer, which represents a distinctive reduction in lifetime over that of eosin bound to bare silica and free in solution [39]. Similarly, a reduction in excited-state lifetime from 1.72 to 0.03 ns was measured for FiTC in Ag@SiO 2 @SiO 2 + FiTC NPs of comparable core size and spacer thickness as compared with corresponding hollow silica nanoshells [41]. These observations are manifestations of the MEF phenomenon, in which metal-fluorophore interactions lead to an increase in the quantum yield of the fluorophore and a decrease in its lifetime.…”
Section: Dependence Of Metal-enhanced Fluorescence On Distancementioning
confidence: 70%
“…When a fluorophore is perturbed by a metallic particle, the plasmonic coupling causes an increase in the molecular radiative decay rate by a factor of , and the metal-enhanced quantum yield (Φ ) and lifetime ( ) values become [30,41] …”
Section: Dependence Of Metal-enhanced Fluorescence On Distancementioning
confidence: 99%
See 1 more Smart Citation